La Broza de espárrago como insumo alternativo sostenido en al fabricación de tableros aglomerados caso: Empresa Tableros Peruanos S.A. - Bocanegra Risco, Carla Adelina (2018)
ABSTRAC The results of the investigation of the asparagus brush as an alternative input sustained in the manufacture of agglomerated boards are presented. The model used in this document is the one planned by Farrel, referring to the distributive efficiency; with some adaptations with the Porter model. The objective was focused on the application of a new process in the manufacture of agglomerated boards, 12 MP mapresa, from alternative supplies of asparagus brush, in a new production function, whose results reached levels of efficacy and efficiency in the product final. The ratio indicators that relate the volume of inputs used, and the availability of the final product, show levels of achievement of efficiency, due to the reduction of production costs, by improving yields. Efficiency indicators, by having a quality end product, by its characteristics in thickness, weight, moisture content, average density, resistance to bending and traction. The resistance to the starting of screws, and swelling, justify the proposed alternative option.